Peptide–Polymer Conjugates: A Promising Therapeutic Solution for Drug-Resistant Bacteria - Xuqiu Shen; Yiyin Zhang; Qijiang Mao; Zhengze Huang; Tingting Yan; Tianyu Lin; Wenchao Chen; Yifan Wang; Xiujun Cai; Yuelong Liang (International Journal of Polymer Science)
By 2050, it is estimated that 10 million people will die of drug-resistant bacterial infection caused by antibiotic abuse. Antimicrobial peptide (AMP) is widely used to prevent such circumstances, for the positively charged AMPs can kill drug-resistant bacteria by destroying negatively charged bacterial cell membrane, and has excellent antibacterial efficiency and low drug resistance. However, due to the defects in low in vivo stability, easy degradation, and certain cytotoxicity, its practical clinical application is limited. The emergence of peptide–polymer conjugates (PPC) helps AMPs overcome these shortcomings. By combining with functional polymers, the positive charge of AMPs is partially shielded, and its stability and water solubility are improved, so as to prolong the in vivo circulation time of AMPs and reduce its cytotoxicity. At the same time, the self-assembly ability of PPC enables it to assemble into different nanostructures to undertake specific antibacterial tasks. At present, PPC is mainly used in wound dressing, bone tissue repair, antibacterial coating of medical devices, nerve repair, tumor treatment, and oral health maintenance. In this study, we summarize the structure, synthesis methods, and the clinical applications of PPC, so as to present the current challenges and discuss the future prospects of antibacterial therapeutic materials.